Developing Science E-Modules based on Scientific reasoning Skills for Primary Education Course - Helmia Tasti Adri; Suwarjono (Jurnal Penelitian Pendidikan IPA, 2023)
This research was conducted to answer the need for teaching materials in natural science education lectures in elementary schools due to the importance of teaching materials that can answer the challenges of technological advances. Where at this time technology is needed to support learning in the classroom so that it is more interactive, interesting, fun and can be done anywhere and anytime. Based on the needs analysis, lecturers have not fully used electronic-based media in lectures, and have not been fully able to produce good and correct electronic-based media or teaching materials. In addition, there is still a lack of teaching materials that can improve students' scientific reasoning abilities. This study aims to develop electronic modules (E-Modules) based on scientific reasoning in natural science education lectures in elementary schools in the Elementary School Teacher Education Study Program. The research design used is research and development with the stages of the ADDIE model which consists of the stages of Analysis, Design, Development, Implementation and Evaluation. The findings of this research are products in the form of Scientific Reasoning E-Modules for natural science education lectures in elementary schools in the Elementary School Teacher Education Study Program. Based on the results of the validation test by the team of experts, the module was declared fit for use and met the criteria as an online teaching module. Based on the test results of the implementation of the use of the module, the module was declared feasible for use and able to facilitate the improvement of students' scientific reasoning abilities based on the results of the pretest and posttest, the t test results showed that t-count was greater than t-table which was (8.30 > 1.691). Therefore it can be concluded that the developed e-module is very useful and can meet the criteria for the need for natural science education lectures in elementary schools. Â